The business of Catholic universities: The renewal strategy - Helen Keefe (Church, Communication and Culture)
Catholic universities, like all universities, face a challenge in the form of the rapidly changing higher education industry. This paper offers a framework based on entrepreneurial principles to help Catholic universities think strategically about how to confront these changes. By assessing some aspects of the current moment in which such universities find themselves, this study proposes that the departure of secular academies away from the concept of the university as a center of truth-seeking oriented to the unity of knowledge and the good life, and the corresponding crisis of purpose plaguing the higher education industry offers Catholic institutions a new opportunity to position themselves as a return to the original university paradigm, a model that is suddenly rare. This paper will then consider the specific comparative advantage held by universities possessing a Catholic identity as compared to their non-Catholic counterparts. We will end by considering a few of the many ways in which this advantage can (and should) be reflected in certain aspects of the university, particularly in fundraising and allocating resources.